Unsettled; Mental Stress in Community-Living Adolescents Who are Seeking Asylum in Australia - Karen Martin; Joanna Sun Wai Ho; Francesca Chia Ning Lau; Yexing Darren Chua; Farida Fozdar (Journal of Behavior Therapy And Mental Health, 2016)
Objectives: This pilot study explored post-traumatic stress symptoms (PTSS) and moderate to severe psychological distress in a small sample of urban community-living adolescents seeking asylum in Australia. The study also examined the relationships between post-traumatic stress symptoms (PTSS) and psychological distress and school and family support and connectedness. Method: A cross-sectional survey examined PTSS (Abbreviated PTSD Checklist), psychological distress (Kessler-5) and school connectedness (California Healthy Kids Survey)53 in 27 adolescents seeking asylum (ages 12-17, mean 15.4) attending two independent secondary schools in Perth, the capital city of Western Australia. Results: In the sample, 63.0% (n=17, 1 missing) of adolescents exceeded the PTSS threshold (i.e. screened positive for Post-traumatic Stress Disorder) and 66.7% (n=18) exceeded the Kessler -5 threshold indicating moderate to severe psychological distress. Overall, 51.9 % (n=14, 1 missing) of adolescents screened above both thresholds suggesting co-occurrence of PTSD and moderate to severe psychological distress. Boys (x̄=15.0, SD=2.9) experienced higher psychological distress scores than girls (x̄=12.1, SD=4.5; p=0.071). Higher perceived support by an adult in school (r=0.13), and at home (r=0.28) were weakly associated with lower PTSS. Less time in Australia was weak-moderately associated with higher psychological distress (r=0.35). Weak associations between higher psychological distress and age (r=0.17) and those who felt more supported by an adult at home (r=0.17) were detected. Conclusion: Approximately two thirds of this group of community-living adolescents who were seeking asylum experienced post- traumatic stress symptoms or psychological distress; and more than one half experienced both. These pilot research findings suggest that adolescents who are seeking asylum and living in the Australian community are at risk of experiencing PTSD and moderate to severe psychological distress; research incorporating larger samples and longitudinal measurement is required. Screening, clinical assessment and examination of the immediate and long term impact, as well as implementation and evaluation of evidence-based mental health interventions, within these populations is also recommended.
Keywords: asylum-seeker